A miniaturized circularly polarized implantable RFID antenna for biomedical applications. Issue 3 (19th December 2019) - Zhang, Yudi; Liu, Changrong; Liu, Xueguan; Zhang, Ke
Abstract: A miniaturized circularly polarized implantable antenna operating at ultrahigh frequency band (902‐928 MHz) for radio frequency identification biomedical monitoring is first presented and experimentally validated in this article. The proposed antenna features a compact volume with a dimension of π × (6) 2  × 1.27 mm 3 by employing an extended ring with meandered lines for size reduction. Moreover, adjusting the length of symmetrical meandered lines can introduce two orthogonal modes, which makes for good performance of circular polarization. Superb impedance matching between the chip and tag antenna is well implemented by applying a modified T‐match stub. In the simulation, the antenna achieves a −10‐dB impedance bandwidth of 42 MHz (902‐944 MHz) and 3‐dB axial‐ratio bandwidth is 53 MHz (892‐945 MHz). Finally, the specific absorption rate is also calculated for human safety and the measured reading range reaches the maximum distance of about 87 cm.